Some geological results from the first five Danish exploration wells in the North Sea. Dansk Nordsø A-1, A-2, B-1, C-1, and D-1 - Rasmussen, Leif Banke (Danmarks Geologiske Undersøgelse III. Række, 1974)
After an introducing survey of the exploration for hydrocarbons on the Danish continental shelf during the period from 1963 to 1968 a lithological and chronostratigraphical description of the first five exploration wells is given. The results are preliminary and they are based on investigations carried out by the staff of the Department of Subsurface Geology at the Geological Survey of Denmark. Deposits of Permian, Triassic, Jurassic, Cretaceous, Tertiary and Quaternary age are proved to occur in the borings. Stratigraphical investigations of the very thick Tertiary sequence in the central part of the North Sea show, that the main part of the sedimentation took place during the younger Miocene (Upper Miocene).